Cellular dynamics of myogenic cell migration: molecular mechanisms and implications for skeletal muscle cell therapies. Issue 12 (19th November 2020) - Choi, SungWoo; Ferrari, Giulia; Tedesco, Francesco Saverio
Abstract: Directional cell migration is a critical process underlying morphogenesis and post‐natal tissue regeneration. During embryonic myogenesis, migration of skeletal myogenic progenitors is essential to generate the anlagen of limbs, diaphragm and tongue, whereas in post‐natal skeletal muscles, migration of muscle satellite (stem) cells towards regions of injury is necessary for repair and regeneration of muscle fibres. Additionally, safe and efficient migration of transplanted cells is critical in cell therapies, both allogeneic and autologous. Although various myogenic cell types have been administered intramuscularly or intravascularly, functional restoration has not been achieved yet in patients with degenerative diseases affecting multiple large muscles. One of the key reasons for this negative outcome is the limited migration of donor cells, which hinders the overall cell engraftment potential. Here, we review mechanisms of myogenic stem/progenitor cell migration during skeletal muscle development and post‐natal regeneration. Furthermore, strategies utilised to improve migratory capacity of myogenic cells are examined in order to identify potential treatments that may be applied to future transplantation protocols. Abstract : This comprehensive review discusses our knowledge on dynamics and mechanisms of myogenic progenitor cell migration during morphogenesis and post‐natal tissue regeneration and provides insights on the possible strategies for the development of safe and efficient cell therapies.